Antituberculosis nanodelivery system with controlled-release properties based on para-amino salicylate–zinc aluminum-layered double-hydroxide nanocomposites - Saifullah B; Hussein MZ; Hussein-; Arulselvan P; Fakurazi S (Dove Medical Press, 2013)
Bullo Saifullah,1 Mohd Zobir Hussein,1 Samer Hasan Hussein-Al-Ali,2 Palanisamy Arulselvan,3 Sharida Fakurazi3,41Materials Synthesis and Characterization Laboratory, 2Laboratory of Molecular Biomedicine, 3Laboratory of Vaccines and Immunotherapeutics, 4Department of Human Anatomy, Universiti Putra Malaysia, Serdang, Selangor, MalaysiaAbstract: We report the intercalation and characterization of para-amino salicylic acid (PASA) into zinc/aluminum-layered double hydroxides (ZLDHs) by two methods, direct and indirect, to form nanocomposites: PASA nanocomposite prepared by a direct method (PASA-D) and PASA nanocomposite prepared by an indirect method (PASA-I). Powder X-ray diffraction, Fourier-transform infrared spectroscopy, and thermogravimetric analysis revealed that the PASA drugs were accommodated within the ZLDH interlayers. The anions of the drug were accommodated as an alternate monolayer (along the long-axis orientation) between ZLDH interlayers. Drug loading was estimated to be 22.8% and 16.6% for PASA-D and PASA-I, respectively. The in vitro release properties of the drug were investigated in physiological simulated phosphate-buffered saline solution of pH 7.4 and 4.8. The release followed the pseudo-second-order model for both nanocomposites. Cell viability (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide [MTT] assays) was assessed against normal human lung fibroblast MRC-5 and 3T3 mouse fibroblast cells at 24, 48, and 72 hours. The results showed that the nanocomposite formulations did not possess any cytotoxicity, at least up to 72 hours.Keywords: drug-delivery system, slow-release nanocarrier, tuberculosis, biocompatible nanocomposites